Pengaruh Citra Merek, Harga, Promosi, dan Kualitas Pelayanan Terhadap Keputusan Penggunaan Jasa Pada Perusahaan J&T Express Kubutambahan - I Made Sukadana; I Ketut Sudarnaya (ARTHA SATYA DHARMA, 2021)
The purpose of this study is to determine the effect of Brand Image, Price, Promotion, and Service Quality on Service Usage Decisions at J&T Express Kubutambahan. This study uses a quantitative approach by using a questionnaire given to all customers who have used the KubuAddan J&T Express expedition service in April 2021 with a total of 96 respondents. The data analysis technique used in this study is a variance-based structural equation model (SEM) or component-based SEM called Partial Last Square (PLS) Visual 3.3.3. Based on the results of the analysis of all the influences studied in this study showed positive and significant results related to the influence of Brand Image showing a positive and significant influence on the Decision to Use Services, then Price had a positive and significant effect on Decisions on Service Use, then Promotion had a positive and significant effect on Service Usage Decisions and Service Quality have a positive and significant impact on Service Use Decisions.